Pembelajaran Matematika dengan STEAM dalam Persepsi Siswa - Arin, Arin; Aisyah, Nyimas; Susanti, Ely; Nuraeni, Zuli (SJME (Supremum Journal of Mathematics Education), 2025)
STEAM is one of the learning approaches that can be used to support students' understanding and knowledge of science, technology, engineering, art, and mathematics can increase, so that this understanding can be used to solve problems and make decisions for the progress of students. However, STEAM is still underutilized in schools. The purpose of this survey research is to describe students' perceptions of learning mathematics using STEAM. The participants in this study were 90 grade 9 students at SMP Negeri 13 Palembang. Participants were selected using voluntary and random sampling techniques. Data were collected using a questionnaire consisting of two parts, namely closed and open statements. Data were analyzed using descriptive statistics with qualitative methods. The results showed that students gave positive and negative responses to the application of STEAM in learning. Students agree that STEAM can increase their motivation and activity in learning. On the other hand, some students choose to apply learning without media because they prefer learning directly delivered by the teacher. This contributes to students' difficulties in mastering math concepts. The results of this study provide useful insights for future research in learning approaches used in teaching.